Pemanfaatan Media Digital Marketing pada Usaha Keripik Pisang di Desa Ledokombo, Jember - Agus Supriono; Riza Oktafiyani; Ariq Dewi Maharani; Tiffany Rahma Abdillah; Soetriono Soetriono; Yuli Hariyati; Anik Suwandari (Jurnal Masyarakat Mengabdi Nusantara, 2025)
The banana chip business in Ledokombo Village, Jember Regency, is one of the sources of livelihood for the local community. However, increasingly fierce business competition has led to a decrease in demand and has an impact on declining turnover of MSME actors. Marketing that is still conventional is one of the factors limiting product reach. This community service activity aims to increase the marketing capacity of MSME actors through digital marketing training. The training was carried out for four weeks with stages: problem analysis, provision of branding and digital marketing materials, assistance in making packaging labels, marketplace accounts (Shopee) and social media (Instagram), as well as monitoring and evaluation. The results of the activity show that MSME actors understand the importance of digital marketing strategies, are able to create "The King" product packaging labels, and have Shopee and Instagram accounts that are actively used for online sales. Business actors are also getting used to operating digital application features that support the marketing process. This activity has a positive impact on increasing product attractiveness and expanding consumer reach. Thus, digital marketing training has proven to be effective as an innovative solution in facing MSME marketing challenges, as well as being a model for local economic empowerment that can be replicated in other regions with similar characteristics.